Evaluating Microeconomic Factors, Financial Crisis, and Stock Price Dynamics: Evidence From MENA Region - N. Al-Malkawi, Husam-Aldin (2020)
The purpose of this chapter is to examine the impact of microeconomic factors and the global financial crisis (GFC) on stock prices in the Middle East and North Africa (MENA) region. The study employs panel data techniques covering a sample of 277 firms listed in seven MENA countries for the period 2000-2015. The empirical model consists of eight microeconomic (firm-specific) variables and a dummy variable to capture the impact of global financial crisis. The results suggest that microeconomic fac tors play a vital role in determining stock prices in the MENA region. More specifically, factors such as return on equity, book value per share, dividend per share, earnings per share, and price-earnings ratio positively influence stock prices, while dividend yield and gearing have negative impact on stock prices. In addition, firm size posits a positive and statistically significant relationship with stock prices. However, the GFC seems to be insignificant determinant of stock prices in the case of MENA countries in the sample studied. This chapter provides several practical implications.